2016
DOI: 10.1080/15592294.2016.1257450
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and supplemental maternal methyl-group donor intake and cord blood DNA methylation

Abstract: Maternal nutrition is critically involved in the development and health of the fetus. We evaluated maternal methyl-group donor intake through diet (methionine, betaine, choline, folate) and supplementation (folic acid) before and during pregnancy in relation to global DNA methylation and hydroxymethylation and gene specific (IGF2 DMR, DNMT1, LEP, RXRA) cord blood methylation. A total of 115 mother-infant pairs were enrolled in the MAternal Nutrition and Offspring's Epigenome (MANOE) study. The intake of methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…Maintenance of the methylome is critical to the integrity of the epigenome. This is regulated via one carbon metabolism and, thus, in turn by nutritional input of methyl donors, such as Met, folate, vitamin B-12, choline and betaine which are substrate providers for many epigenetic processes (12,13). Little is known about how nutrients affect epigenetic processes in CKD.…”
Section: What Is Epigenetics and How Is It Regulated?mentioning
confidence: 99%
“…Maintenance of the methylome is critical to the integrity of the epigenome. This is regulated via one carbon metabolism and, thus, in turn by nutritional input of methyl donors, such as Met, folate, vitamin B-12, choline and betaine which are substrate providers for many epigenetic processes (12,13). Little is known about how nutrients affect epigenetic processes in CKD.…”
Section: What Is Epigenetics and How Is It Regulated?mentioning
confidence: 99%
“…Research in mammals has further investigated the effects of maternal nutrition on the offspring epigenome and also determined that maternal imprinting via epigenetic modifications are, in part, responsible for the effects on offspring health and development (Cooper et al, ; El Hajj, Schneider, Lehnen, & Haaf, ; Fowden, Coan, Angiolini, Burton, & Constancia, ; Ivanova, Chen, Segonds‐Pichon, Ozanne, & Kelsey, ; Jousse et al, ). Additional studies have confirmed that the maternal intake of nutrients essential for cellular methylation reactions such as methionine, choline, and folate can alter epigenetic patterns in the offspring (Amarasekera et al, ; Medici et al, ; Pauwels et al, ). Therefore, research in mammals and fish collectively support that epigenetic modifications may be partially responsible for the nutritional programming response observed from methionine and choline supplementation in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…[ 18 ] Previous study reported that maternal intake of methyl donors, including folate, betaine and choline, during different gestation period alters epigenetic modifications of many imprinted genes in the genomic DNA isolated from cord blood. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%